Strategies for overcoming resistance to Bruton's tyrosine kinase inhibitor zanubrutinib - Dostálová, Hana; Kryštof, Vladimír (Hematological oncology, 2024)
Bruton's tyrosine kinase (BTK) inhibitors have revolutionized the treatment of B-cell malignancies. They target BTK, a key effector in the B-cell receptor (BCR) signaling pathway, crucial for B-cell survival and proliferation. The first-in-class irreversible BTK inhibitor, ibrutinib, was approved for various B-cell malignancies but has limitations due to off-target effects. Second-generation inhibitors, such as acalabrutinib and zanubrutinib, offer improved selectivity and reduced side effects. However, resistance to BTK inhibitors, driven by BTK mutations, remains a challenge. Combinatorial therapies with PI3K inhibitors, immune checkpoint inhibitors, BH3 mimetics, and anti-CD20 antibodies show promise in overcoming resistance. Noncovalent BTK inhibitors and proteolysis-targeting chimeras (PROTACs) are emerging strategies with potential to combat resistance. Overall, advancements in BTK-targeted therapies provide hope for improved outcomes in patients with B-cell malignancies and a promising avenue to address drug resistance. Further research is needed to optimize combination therapies and identify optimal treatment regimens.
Keywords: Protein Kinase Inhibitors; inhibitory tyrosinkinasy; Tyrosine Kinase Inhibitors; Lymphoma, B-Cell; Piperidines; chemorezistence; Pyrazoles; Drug Resistance, Neoplasm; B-buněčný lymfom; Pyrimidines; lidé; Agammaglobulinaemia Tyrosine Kinase; pyrazoly; inhibitory proteinkinas; piperidiny; pyrimidiny; Humans; proteinkinasa BTK